A new vector for efficient gene targeting to the pyrG locus in Aspergillus niger - Arentshorst, Mark (Fungal Biol Biotechnol, 2015)
BACKGROUND: The possibility for efficient gene targeting for the controlled integration of DNA constructs is an important tool in fungal genetics. FINDINGS: In this study, we report a new targeting vector based on the pyrG marker in Aspergillus niger. The DNA sequence to be targeted is surrounded by two fragments of the pyrG gene to allow homologous recombination of the recombinant DNA at the pyrG locus. The 5’ end of the targeting cassette contains a non-functional truncated pyrG open reading frame (first 112 bases deleted) and the 3’ untranslated region (3’ UTR). At the 3’ end, the targeting cassette consists of the 3’ flanking region of the pyrG gene. A unique NotI site between the flanks allows the insertion of a gene of interest. The linearized targeting cassette is transformed to the A. niger pyrG mutant strain AB4.1 or a derivative thereof. By using a constitutively expressed luciferase reporter gene (mluc) as an example, it is shown that the targeting system is efficient as 4 out of 6 (67%) AB4.1 transformants and 51 out of 66 (77%) MA169.4 (ku70 (−)) transformants contained the reporter gene at the pyrG locus. A luciferase (lux) activity assay, performed with independently obtained transformants in which the mluc reporter was integrated at the pyrG locus, showed comparable and reproducible lux activities. CONCLUSION: The new pyrG targeting vector is an important improvement to the existing method for gene targeting in A. niger. Although the vector is specific for A. niger, the presented design and approach is easily applicable for constructing integration vectors for other fungi.